Factors Affecting Satisfaction and Loyalty Toward University Education: A Case Study of Students at Public Universities in Chengdu, China - Sun, Lijie (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This paper examines the factors influencing educational satisfaction and loyalty toward university education in public universities in Chengdu, China. It presents a case study investigating the perspectives of current students. The research focuses on the causal relationships between Teaching Staff (TS), Curriculum (CC), Infrastructure Facilities (IF), Placement Services (PS), Institutional Image (IM), Student Satisfaction (SS), and Student Loyalty (SL) in higher education. Research design, data and methodology: This study employs a quantitative approach (N=503) to survey university students. The questionnaire’s reliability and validity were assessed through IOC and pilot testing. A combination of purposive, stratified random, and convenience sampling was used to target students at Sichuan University, China. Data were collected via an online questionnaire, with valid responses analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: Research indicates that teaching staff, curriculum, infrastructure, image, and placement services significantly influence student satisfaction, which in turn affects student loyalty. Among these factors, faculty has the least impact on student satisfaction. Conclusions: All seven hypotheses in this study aligned with the research objectives. These findings can help higher education administrators, particularly in public universities in Chengdu, western China, assess and develop strategies to enhance student satisfaction and loyalty, ultimately supporting the growth of public universities in the region.